ChemInform Abstract: Microwave Assisted Facile Synthesis of 1‐Amidoalkyl‐2‐naphthols Catalyzed by Stannous Oxide Nanoparticles. Issue 21 (6th May 2016) - Singh, Rajesh Kumar; Bala, Renu; Kumar, Sahil
Abstract: The stannous oxide nanoparticles are an efficient, inexpensive, recyclable and reusable, eco‐friendly heterogenous catalyst.